2002
DOI: 10.1068/p3205
|View full text |Cite
|
Sign up to set email alerts
|

The Limited Capacity of Humans to Identify the Components of Taste Mixtures and Taste – Odour Mixtures

Abstract: The capacity of humans to identify the components of taste mixtures and odour-taste mixtures was investigated in two experiments. Subjects were trained to identify the components presented alone and to use a 'yes/no' procedure to identify them in mixtures. All stimuli were presented with a retronasal (by mouth) technique. A maximum of three tastants were identified in both types of mixtures, only one tastant was identified in five-component taste mixtures, and no component was identified in four-component odou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 20 publications
2
44
1
Order By: Relevance
“…If pure substances were to each have just two resolvable, distinguishable dominant odor notes of similar strength [20], an array of 350 different human olfactory receptors [19] could theoretically allow the recognition of more than 100,000 different chemicals. Predictably, because, unlike tastes, they are so numerous, odor qualities are difficult to bring to mind unless linked to actual objects in one's personal experience [10,11,37] and appear countless and difficult, if not impossible, to classify [9].…”
Section: Dynamic Odor Coding Assures Odor-quality Constancymentioning
confidence: 99%
“…If pure substances were to each have just two resolvable, distinguishable dominant odor notes of similar strength [20], an array of 350 different human olfactory receptors [19] could theoretically allow the recognition of more than 100,000 different chemicals. Predictably, because, unlike tastes, they are so numerous, odor qualities are difficult to bring to mind unless linked to actual objects in one's personal experience [10,11,37] and appear countless and difficult, if not impossible, to classify [9].…”
Section: Dynamic Odor Coding Assures Odor-quality Constancymentioning
confidence: 99%
“…It is well known 12 that multiple taste stimuli are hard to discriminate in the context of complex flavor stimuli, with suppression of perceived intensity of dissimilar tastes [45]. Notably, the ability to detect 14 the presence of MSG in mixtures containing more than two other taste stimuli was at chance level [46]. Thus the complexity of the current flavor stimuli may have masked subtle changes 16 in perceived sensory quality brought about by the association of the overall flavor of the soup and the taste of MSG in the MSG-trained group.…”
mentioning
confidence: 99%
“…When three or four arbitrarily chosen taste or odour compounds are mixed, the suppressive interactions become so strong that the components become difficult even to recognise (Laing, Link, Jinks & Hutchinson, 2002). The compounds can only mask each other (Cain et al, 1995;Marshall et al, 2006).…”
Section: Configured Ideal Points Mixture Statisticsmentioning
confidence: 99%
“…The effect was reduced by familiarisation with the mixtures and so it was suggested that learning to configure the separate tastes or smells could remove confusion among them (Laing et al, 2002). A major review of the literature on recognition of odours concluded that each profile of receptors stimulated repeatedly stimulated receptors was stored in memory as a configuration that could be compared with subsequent mixtures of volatiles (Stevenson & Boakes, 2003).…”
Section: Configured Ideal Points Mixture Statisticsmentioning
confidence: 99%